2014
DOI: 10.1016/j.drugalcdep.2014.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Use trajectories of amphetamine-type stimulants (ATS) in Shanghai, China

Abstract: Background Although amphetamine-type stimulant (ATS) use is an important issue that has caused growing concerns in China as well as other countries, the knowledge of long-term patterns of ATS use in China is limited. This study explored long-term patterns of ATS use in Shanghai, China, and compared the differences by ATS use trajectory groups, seeking to identify risk factors that have implications for the development of targeted intervention programs. Methods A total of 377 ATS users were recruited from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 32 publications
(30 reference statements)
0
18
0
Order By: Relevance
“…Four studies investigated the association between stimulant use and SIB. In China, past suicidal behaviour was positively associated with amphetamine-type stimulant (ATS) use [ 101 ]. A study from Iran reported a null association between ATS use and suicide attempt [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies investigated the association between stimulant use and SIB. In China, past suicidal behaviour was positively associated with amphetamine-type stimulant (ATS) use [ 101 ]. A study from Iran reported a null association between ATS use and suicide attempt [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…All four studies made use of a cross-sectional design and were assessed to be of high-quality. The study regions included EAP [ 101 ], LAC [ 102 ], MNA [ 70 ], and SSA [ 66 ], while no studies were from the ECA or SAS study regions.…”
Section: Resultsmentioning
confidence: 99%
“…Depression is another prevalent psychiatric symptom among ATS-dependent individuals. Evidence provided a result to support the consequence that more than half of the ATS dependents had depression symptoms (Du et al, 2014 ). Sleep quality and mood may play a role in the course of ATS use disorders and affect the outcome of treatment (Putnins et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…ATS use has been correlated with serious health consequences, such as cognitive impairment, poor physical status, high risk of mortality, and increased social burden (Chen et al, 2015 ). Recently, the population of ATS use in China has grown substantially (Du et al, 2014 ). The registered drug use identified as methamphetamine (MA) user increased from 29 to 43.8% in 2014 (Zhu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation